Creating an Alternate Field Experience Framework for University-Based Preservice Teacher Education in the COVID-19 Nigeria - Rufai, Saheed Achmad; Luqman Lekan Adedeji; Bello Musa; Uthman Animashaun; Sanni Aliu Saidi; Morufu Sanni Okusanya (Indonesian Journal of Social Research (IJSR), 2022)
It is widely reported that several institutions of higher learning in various parts of the world attempted to mitigate the risks of learning disruptions occasioned by school closures, by switching to the online system of education. In the Nigerian context however the field experience component of teacher education witnessed an unprecedented setback as the online system that was later activated in some universities failed to factor the component into the alternative arrangement. Given that the present COVID-19 is not likely to be the last, as established by various reports including the World Bank December, 2021 document, the exercise may have to be suspended or delayed whenever there are emergency school closure. This paper attempts to formulate a COVID-19 compliant field experience framework for the Nigerian setting. The formulation is based on findings from a survey of emerging COVID-19 focussed alternatives and preservice teachers. The paper whose context comprises three Nigerian public universities where the lead researcher was, at different times, a field experience assessor employs a combination of a survey method, the philosophical method, observation, document analysis, and creative synthesis. The literature, findings from the survey and online interviews with student teachers constitute the bases of the formulation.